KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI KATALISATOR BUDAYA ORGANISASI DAN KOMITMEN KERJA DALAM MENDORONG INOVASI DI ORGANISASI PENDIDIKAN - Rahmah, Aulia; Sari, Indah Puspita; Nurdohiyah, Nurdohiyah; Aslamiah, Aslamiah; Cinantya, Celia (Jurnal Manajemen Pendidikan, 2025)
A Transformational leadership is a form of leadership style that focuses on inspiring, motivating, and developing the maximum potential of each team member. Rather than simply giving directions or instructions, leaders who adopt this style are committed to creating profound positive change, not only in their team dynamics, but also in the entire organizational structure. This article aims to comprehensively examine transformational leadership organizational culture, work commitment in driving innovation in educational organizations through a literature review. This research highlights the important role of transformational leadership in motivating, empowering and developing individuals in the organization to achieve organizational goals to encourage innovation in educational organizations. The results of the literature review indicate that transformational leaders are not only able to improve performance and encourage innovation, but also build an organizational culture that supports collaboration, openness to change, and member empowerment especially in educational organizations. The practical implications of this study emphasize the importance of developing transformational leadership skills to create an environment that motivates members, encourages innovation, and ensures sustainability in organizations.